2022
DOI: 10.3390/atmos13122053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Greenhouse Gas Emissions into the Atmosphere from the Northern Peatlands Using the Wetland-DNDC Simulation Model: A Case Study of the Great Vasyugan Mire, Western Siberia

Abstract: The peatlands of Western Siberia occupy an area of about 1 million km2 and act as important regulator of carbon exchange between the earth and the atmosphere. Extrapolation of the results of discrete field measurements of CO2 fluxes in bog ecosystems to such a territory is a difficult task, and one of the ways to overcome it is to use a simulation model such as DNDC. However, using this model with a specific territory requires ground verification to confirm its effectiveness. Here, we tested the DNDC model on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Statistical processing of the results from the Wetland-DNDC simulation model showed that the modeled hydrothermal factors (T, P, and WT) are not correlated with each other, and the model efficiency is high (R 2 = 0.675)-as shown in the earlier publication [16]-therefore, our next target was a computer simulation of different hydrothermal scenarios and estimation of greenhouse gas fluxes under the change of these hydrothermal parameters (T, P, and WT).…”
Section: Methodsmentioning
confidence: 60%
See 4 more Smart Citations
“…Statistical processing of the results from the Wetland-DNDC simulation model showed that the modeled hydrothermal factors (T, P, and WT) are not correlated with each other, and the model efficiency is high (R 2 = 0.675)-as shown in the earlier publication [16]-therefore, our next target was a computer simulation of different hydrothermal scenarios and estimation of greenhouse gas fluxes under the change of these hydrothermal parameters (T, P, and WT).…”
Section: Methodsmentioning
confidence: 60%
“…At the land surface, the Sphagnum mosses cover 95 to 100%, of which 80% is contributed by Sphagnum fuscum, with little presence of Sphagnum divinum and Sphagnum angustifolium. Some more details on the study site are presented in our earlier publication [16].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations